1998
DOI: 10.1097/00005650-199808000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Physician Retention in Community and Migrant Health Centers

Abstract: The study demonstrates the value of discrete-time survival analysis in addressing questions related to the tenure of primary care physicians in Community Health Centers, making it possible to use data from physicians whose Community Health Center careers began before or ended after a give measurement window. Second, the study measured primary care physician tenure, providing center directors with a yard-stick against which to compare their own center's performance. Finally, the data provided some help in tryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…Inasmuch as the centers are operated by nonprofit organizations that seek to provide services for poor people, staffing often relies upon physicians from the National Health Service Corps. One study of primary physician tenure at CHC-MHP health centers found that the median tenure was just three years (63). Obviously, if physician recruitment and retention is a serious problem, the imposition of language or cultural familiarity requirements during recruitment are out of the question.…”
Section: Access To Health Care Servicesmentioning
confidence: 99%
“…Inasmuch as the centers are operated by nonprofit organizations that seek to provide services for poor people, staffing often relies upon physicians from the National Health Service Corps. One study of primary physician tenure at CHC-MHP health centers found that the median tenure was just three years (63). Obviously, if physician recruitment and retention is a serious problem, the imposition of language or cultural familiarity requirements during recruitment are out of the question.…”
Section: Access To Health Care Servicesmentioning
confidence: 99%
“…2,6 Discrete-time survival analysis of physicians working in community and migrant health services in the United States (US) found that the mean period of tenure of primary care physicians working in these areas was only 3 years. 7 Working with disadvantaged and marginalised patients can pose challenges for physicians, whose roles often expand to include advocacy and coordination of complex patient journeys through the health system. 2,8 When these roles are shoehorned into busy general practices, GPs report feeling overwhelmed.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Physicians have compelling reasons to avoid practicing among the poor. Physicians who choose to work in underserved settings often forgo academic opportunities, professional prestige, 7 and free time, 10 and accept reduced salaries, diminished control over the work environment, 4 and increased bureaucratic interference. 10 These and other extrinsic 11,12 and objective 13 workplace characteristics diminish the appeal of underserved settings.…”
Section: Introductionmentioning
confidence: 99%